Evaluation of suspicious breast lesions with diffusion kurtosis MR imaging and connection with prognostic factors. Issue 145 (December 2021) - Yang, Zhen Lu; Li, Yan; Zhan, Chen Ao; Hu, Yi Qi; Guo, Yi Hao; Xia, Li Ming; Ai, Tao
Highlights: DKI is not superior to conventional DWI in differentiating suspicious breast lesions. The specificities of ADC and Dapp are both higher than that of DCE-MRI. The DWI/DKI-parameters can reflect receptor and lymph node status of breast cancers. Abstract: Purpose: To investigate the additional value of DKI in discriminating suspicious breast lesions on DCE-MRI, as compared with conventional DWI; and to explore connection between DKI-parameters and prognostic factors of breast cancers. Methods: The institutional review board approved this retrospective study and written informed consent was waived. Totally, 300 women (mean age, 43.2 ± 10.4 years) with suspicious breast lesions on DCE-MRI were enrolled from November 2014 to September 2019. With pathology as reference, performance of ADC, Kapp and Dapp in discriminating suspicious breast lesions were analyzed by receiver operating characteristic (ROC) analysis with area under ROC curve (AUC). The specificities of parameters were compared by Chi-square test. The ADC, Kapp and Dapp of breast cancers with different receptor status were compared using Student's t or Mann-Whitney U or Kruskal-Wallis test. Results: There were 344 suspicious breast lesions (220 malignant, 124 benign) in 300 women. No significant differences were found for AUCs of ADC and DKI-parameters in discriminating suspicious breast lesions (0.882 vs. 0.888, p = 0.480). The specificities were significantly higher with ADC and Dapp than that with DCE-MRI (p = 0.003 and 0.005). The ADC, Kapp and Dapp were correlated with HER2 expression and lymph node status, and ADC and Kapp differed between ER-positive and negative tumors (all p < 0.05). Except Kapp, DKI/DWI-parameters showed relation with Ki-67 expression. None of the DKI/DWI-parameters showed relation with lesion grade (all p > 0.05). Conclusion: The more complicated and time-consuming DKI is not superior to conventional DWI in differentiating suspicious breast lesions and reflecting prognostic information of breast cancer.